2004
DOI: 10.1002/yea.1155
|View full text |Cite
|
Sign up to set email alerts
|

The cell wall sensor Wsc1p is involved in reorganization of actin cytoskeleton in response to hypo‐osmotic shock in Saccharomyces cerevisiae

Abstract: The cell wall is essential to preserve osmotic integrity of yeast cells. Some phenotypic traits of cell wall mutants suggest that, as a result of a weakening of the cell wall, hypo-osmotic stress-like conditions are created. Consequent expansion of the cell wall and stretching of the plasma membrane trigger a complex response to prevent cell lysis. In this work we examined two conditions that generate a cell wall and membrane stress: one is represented by the cell wall mutant gas1 and the other by a hypo-osmot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
34
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 56 publications
(62 reference statements)
2
34
0
1
Order By: Relevance
“…After the N-glycosidase treatment, the apparent molecular masses of WscA-HA and WscB-HA decreased to 43 to 48 kDa and 48 to 63 kDa, respectively. The size differences before and after N-glycosidase treatment were consistent with the existence of three N-glycosylation sites with the typical N-glycan structure [Man (5)(6)(7)(8)(9)(10)(11)(12) GlcNAc 2 ] that has been described for Aspergillus glycoproteins (1,19,49,50). Thus, our results suggest that both WscA and WscB are N-glycosylated in A. nidulans.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…After the N-glycosidase treatment, the apparent molecular masses of WscA-HA and WscB-HA decreased to 43 to 48 kDa and 48 to 63 kDa, respectively. The size differences before and after N-glycosidase treatment were consistent with the existence of three N-glycosylation sites with the typical N-glycan structure [Man (5)(6)(7)(8)(9)(10)(11)(12) GlcNAc 2 ] that has been described for Aspergillus glycoproteins (1,19,49,50). Thus, our results suggest that both WscA and WscB are N-glycosylated in A. nidulans.…”
supporting
confidence: 88%
“…Phylogenetic analysis showed that WscA and WscB can be classified into the Wsc1 and Wsc4 branches, respectively, with relatively high bootstrap values (data not shown). Wsc1 localizes in the plasma membrane and acts as a main sensor transducer for the CWI signaling pathway in S. cerevisiae (12,25,30). On the other hand, Wsc4 localizes in the endoplasmic reticulum (ER) and is involved in the translocation of soluble secretory proteins and the insertion of membrane proteins into the ER membrane.…”
mentioning
confidence: 99%
“…Under conditions such as heat shock or damage of the cell wall, the actin cytoskeleton is rapidly depolarized to suspend polarized cell growth and to repair damage (Levin, 2011). Consistent with a recent report (Gualtieri et al, 2004), the cortical actin cytoskeleton was rapidly depolarized upon transient (20 min) hypotonic shock, and eventually repolarized within 3 h in wild type cells (Fig. 4D).…”
Section: Ypk1/ypk2 Support Rho1 Localization To the Bud Cortex Duringsupporting
confidence: 89%
“…Stresses include rapid changes in external osmolarity and temperature and insults to the cell wall, to DNA, and to the actin cytoskeleton. Some stresses have pleiotropic effects; for example, hyper-and hypoosmotic stresses cause not only ion imbalance and cell shrinkage or swelling but also a rapid although transient depolarization of the actin cytoskeleton (7,23,26,60). Perturbations of the actin cytoskeleton are known to arrest dividing cells until the damage is repaired (25).…”
mentioning
confidence: 99%
“…For example, repolarization of the actin cytoskeleton following a hypoosmotic shock involves the cell wall sensors Wcs1p and Mid2p, which are both potential activators of the Pkc1p-Slt2p cell wall integrity pathway (23). Repolarization of the actin cytoskeleton following a hyperosmotic shock requires the activity and proper polarized localization of the MEKKK Ssk2p of the Sln1p branch of the Hog1-dependent pathway (60).…”
mentioning
confidence: 99%